A case of secondary choroidal neovascularization in inactive choroidal tuberculoma - Farhana Ibrahim; Nor Azita AT; Hamisah I (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Ocular tuberculosis is an ocular infection caused by Mycobacterium tuberculosis (TB). About 5-10% of ocular inflammation cases are caused by ocular TB. Spectrum of ocular TB is diverse, affecting any part of the adnexa, different layers and structures of the globe, orbital contents, optic nerve to the orbital apex posteriorly. It can be associated with or without systemic manifestation. Posterior uveitis is the most common presentation of ocular tuberculosis. Subretinal haemorrhage secondary to choroidal neovascularization (CNV) is a rare complication in ocular tuberculosis. We report a rare case of secondary choroidal neovascularization in a 9-year-old boy with bilateral eye choroidal tuberculoma with underlying miliary tuberculosis. He was treated with intravitreal ranibizumab and intravitreal recombinant-tissue plasminogen activator (r-TPA) injection. The CNV resolved, however, vision was poor due to atrophic fovea.